Analisis Perbandingan Sistem Hukum Konstitusi Indonesia dan Malaysia dalam Pemilihan Kepala Pemerintahan - Sulthoni Ajie Sahidin; Handar Subhandi Bakhtiar (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
The selection of the head of government is a fundamental aspect of the constitutional system that reflects the political and legal character of a state. Although Indonesia and Malaysia share similar historical roots, they adopt significantly different systems of governance. This study addresses two core issues which are about the structure and mechanism of executive and legislative power, and the impact of the presidential threshold and parliamentary coalition on governmental stability. Using a normative juridical method with statutory and comparative approaches, the findings reveal that Indonesia, under a presidential system, applies a nomination threshold to ensure political stability, yet it may restrict political access. Meanwhile, Malaysia’s parliamentary system is more flexible but vulnerable to instability due to coalition dynamics. This study recommends a reassessment of Indonesia’s presidential threshold for a more democratic process and strengthening of political stability mechanisms in Malaysia.